Analisis Persepsi Mahasiswa Mengenai Dampak Perdagangan Internasional terhadap Strategi Pembangunan Nasional (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to describe students' perceptions of the impact of international trade on national development strategies amidst economic globalization. In this context, cross-border trade plays an important role in accelerating economic growth and improving the competitiveness of domestic products. Students' understanding, as part of the generation that will drive the future economy, is crucial to assess the extent to which they perceive the relationship between international trade and national development. This research uses a descriptive quantitative approach with data collection techniques through the distribution of questionnaires to economics students. The findings show that the majority of students have a positive perception of the contribution of international trade, especially in terms of increasing exports, absorbing foreign investments, and creating job opportunities. However, a small proportion of respondents also noted the risks of dependency on global markets, which could affect domestic economic stability. Overall, these findings emphasize the importance of international trade in supporting sustainable and inclusive national development, balancing the benefits of globalization with domestic economic protection.